Critical thinking in mathematics education: A bibliometric analysis - Yanuari, Nuke Fitri; Turmudi, Turmudi (SAINTIS Publishing, 2023)
Mathematical critical thinking is one of the most important skills that students must possess. The ability to think critically in mathematics is an essential skill that can be developed through effective teaching practices and student engagement. This article presents the questions to be investigated regarding critical thinking using bibliometric analysis. Bibliometric analysis is a method used to analyze research articles related to a chosen topic. The data source for this analysis is Scopus. The search was filtered by subject area, document type, language, and publication year. According to the results from Scopus, a total of 148 documents related to mathematical critical thinking were obtained from 2019 until May 2023. Based on the co-occurrence analysis of authors' keywords, besides 'critical thinking' and 'critical thinking skills', 'secondary school' and 'secondary education' appeared most frequently, with 6 occurrences. These trends in the number of articles can provide insights into the research interests in this field.